INFLUENCE OF EXTRAGENITAL PATHOLOGY ON THE ORIGIN AND EXPRESSION OF ANTIPHOSPHOLIPID SYNDROME AND NUMBER OF REPRODUCTIVE LOSSES - Кравченко, Елена Николаевна; Гончарова, Анастасия Александровна (Mother and Baby in Kuzbass, 2019)
Objective – to study the effect of extragenital pathology on the occurrence and severity of antiphospholipid syndrome (APS) and the number of reproductive losses.Materials and research methods. 137 cards of women with a history of pregnancy termination were analyzed, divided into 2 groups according to the principle of presence/absence of plasmapheresis in the treatment regimen at the stage of pregravid preparation, followed by ranking into 2 subgroups according to the principle of presence/absence of TORCH infection activity.Results. Among extragenital pathology, the correlation of which had diagnostic, pathogenetic and statistical significance as a result of the analysis of all indicators, autoimmune thyroiditis, infectious pathology and pathology of ENT organs were identified. A strong direct correlation was observed in women with AFLS between the level of IgG to b2-glycoprotein-1 and the pathology of ENT organs. The pair «Autoimmune thyroiditis – IgG b2-glycoprotein-1» was characterized by a different level of correlation: in women with a single pregnancy loss, this relationship was characterized as a direct correlation of a weak or moderate degree. The presence of an inverse correlation between the frequency of occurrence of seasonal infectious diseases, not exceeding the average population values and the level of lupus anticoagulant, was revealed. In women with a single gestational loss, this relationship was characterized as an inverse weak correlation. In women with the usual loss of pregnancy with AFS without signs of TORCH infection, a weak negative correlation was noted.Conclusion. Changes in the correlation between the content of specific antiphospholipid antibodies in the blood and extragenital pathology in women with habitual miscarriage and a different number of gestational losses indicate additional mechanisms for the development of miscarriage in women who have had repeated miscarriages, which must be taken into account in clinical practice at the pregravid stage.
Keywords: antiphospholipid syndrome; miscarriage; pregnancy; habitual miscarriage; plasmapheresis; TORCH infection